Ba4Ta2O9 oxide prepared from an oxalate-based molecular precursor-characterization and properties - Androš, Lidija; Jurić, Marijana; Popović, Jasminka; Šantić, Ana; Lazić, Predrag; Benčina, Metka; Valant, Matjaz; Brničević, Nevenka; Planinić, Pavica (Inorganic chemistry, 2013)
A novel heterometallic oxalate-based compound, {Ba2(H2O)5[TaO(C2O4)3]HC2O4}·H2O (1), was obtained by using an (oxalato)tantalate(V) aqueous solution as a source of the complex anion and characterized by X-ray single-crystal diffraction, IR spectroscopy, and thermal analysis. Compound 1 is a three-dimensional (3D) coordination polymer with the Ta atom connected to eight neighboring Ba atoms through the oxalate ligands and the oxo oxygen group. Thermal treatment of 1 up to 1200 °C leads to molecular precursor-to-material conversion that yields the mixed-metal γ-Ba4Ta2O9 phase. This high-temperature γ-Ba4Ta2O9 polymorph has the 6H-perovskite structure (space group P6(3)/m), in which the Ta2O9 face-sharing octahedral dimers are interconnected via corners to the regular BaO6 octahedra. To date, γ-Ba4Ta2O9 has never been obtained at room temperature, because of the reduction of symmetry (P6(3)/m → P2(1)/c) that usually occurs during the cooling. Spectroscopic, optical, photocatalytic, and electrical properties of the obtained γ-Ba4Ta2O9 phase were investigated. In addition to the experimental data, an absorption spectrum and band structure of the γ-Ba4Ta2O9 polymorph were calculated using density functional theory.